2018
DOI: 10.1021/acs.biochem.8b01166
|View full text |Cite
|
Sign up to set email alerts
|

The m6A Writer: Rise of a Machine for Growing Tasks

Abstract: The central dogma of molecular biology introduced by Crick describes a linear flow of information from DNA to mRNA to protein. Since then it has become evident that RNA undergoes several maturation steps such as capping, splicing, 3'-end processing and editing. Likewise, nucleotide modifications are common in mRNA and are present in all organisms impacting on the regulation of gene expression. The most abundant modification found in mRNA is N6-methyladenosine (m 6 A). Deposition of m 6 A is a nuclear process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 162 publications
(660 reference statements)
5
145
1
1
Order By: Relevance
“…Generally, the enzymatic core METTLE3 and methyltransferase like 14 (METTL14), as well as Wilms' tumor 1-associated protein (WTAP), Virilizer like m6A methyltransferase associated protein (VIRMA/KIAA1429), RNA-binding motif protein 15 (RBM15), RNA-binding motif protein 15B (RBM15B/OTT3), zinc finger CCCH domain-containing protein 13 (ZC3H13, as known as Flacc and KIAA0853) and Hakai (also known as Cbl proto-oncogene like 1, CBLL1) constitute of a methyltransferase complex, also known as m 6 A-METTL associated complex (MACOM), that can mediates the m 6 A methylation. Meanwhile, two demethylases, Fat mass and obesity-associated protein (FTO) and ALKBH5, catalyze the m 6 A demethylation [37][38][39][40][41][42].…”
Section: Rna M 6 a Modification In Gbmmentioning
confidence: 99%
“…Generally, the enzymatic core METTLE3 and methyltransferase like 14 (METTL14), as well as Wilms' tumor 1-associated protein (WTAP), Virilizer like m6A methyltransferase associated protein (VIRMA/KIAA1429), RNA-binding motif protein 15 (RBM15), RNA-binding motif protein 15B (RBM15B/OTT3), zinc finger CCCH domain-containing protein 13 (ZC3H13, as known as Flacc and KIAA0853) and Hakai (also known as Cbl proto-oncogene like 1, CBLL1) constitute of a methyltransferase complex, also known as m 6 A-METTL associated complex (MACOM), that can mediates the m 6 A methylation. Meanwhile, two demethylases, Fat mass and obesity-associated protein (FTO) and ALKBH5, catalyze the m 6 A demethylation [37][38][39][40][41][42].…”
Section: Rna M 6 a Modification In Gbmmentioning
confidence: 99%
“…Many of these factors are also conserved and include the following proteins, denoted with plant name first and mammalian homolog following a slash (see Figs. 1 and 2 for additional details): the splicing factor FKBP12 Interacting Protein37 (FIP37/WTAP; Vespa et al, 2004;Zhong et al, 2008;Liu et al, 2014;Ping et al, 2014;Schwartz et al, 2014b;Shen et al, 2016;R u zička et al, 2017); the protein VIRILIZER (VIR/KIAA1429), originally identified in Drosophila melanogaster (Niessen et al, 2001;Ortega et al, 2003;Schwartz et al, 2014b;R u zička et al, 2017); the putative ubiquitin E3 ligase HAKAI/CBLL1 (Horiuchi et al, 2013;R u zička et al, 2017); the Zn finger protein ZC3H13 (Guo et al, 2018;Knuckles et al, 2018;Wen et al, 2018) without orthologs in plants (Balacco and Soller, 2019); and the RNAbinding proteins RBM15A/B (Horiuchi et al, 2013;Yan and Perrimon, 2015;Lence et al, 2016;Patil et al, 2016). Interestingly, the closest plant homolog of RBM15A/B is FLOWERING LOCUS PA (FPA), an RNA-binding protein required for the control of flowering time (Schomburg et al, 2001).…”
Section: Occurrence Of M 6 a In Plant Transcriptomesmentioning
confidence: 99%
“…YTHDC2 is specific to mammals and contains several other folded domains in addition to the YTHDC domain (Bailey et al, 2017;Wojtas et al, 2017;Kretschmer et al, 2018), while YTHDC1 has long N-and C-terminal IDRs (Patil et al, 2016). YTHDF-and YTHDC1-type proteins are found in many eukaryotes (Balacco and Soller, 2019), including plants, whose genomes encode more YTH domain proteins than other organisms (Li et al, 2014a;Scutenaire et al, 2018). For example, 13 YTH domain-containing proteins are encoded in Arabidopsis (Fig.…”
Section: Reading M 6 Amentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation at the N6 position in adenosine (m 6 A) is the most common internal modification in 38 eukaryotic mRNA. A methyltransferase complex composed of METTL3, METTL14, WTAP, VIRMA, and 39 other cofactors catalyzes methylation at DRACH/DRAC motifs, primarily in the last exon (1,2). Most m 6 A 40 methylation occurs during transcription (3).…”
Section: Introduction 37mentioning
confidence: 99%